1992
DOI: 10.1099/0022-1317-73-1-113
|View full text |Cite
|
Sign up to set email alerts
|

Role of Epstein-Barr virus and interleukin 6 in the development of lymphomas of human origin in SCID mice engrafted with human tonsillar mononuclear cells

Abstract: Mice with severe combined immunodeficiency were inoculated intraperitoneally with 50x 106 human tonsillar mononuclear cells (hu-TMCs) from EpsteinBarr virus (EBV) antibody seropositive or seronegative human subjects. Between 5 and 11 weeks later, 29.4% (10/34) of mice injected with hu-TMCs from EBV seropositive donors, but none of 34 animals receiving hu-TMCs from EBV seronegative donors, developed intraabdominal and/or intrathoracic tumours (P, 0.002). By means of in situ hybridization using alpha satellite D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

1993
1993
1998
1998

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 56 publications
2
5
0
Order By: Relevance
“…Kinetic studies of the effect of human immunoglobulin preparations on in vitro-induced monokine production indicated a sustained, significant inhibition of IL-6 production in the cultures supplemented with y-globulin (Anderson and Anderson, 1990). In agreement with Nadal et al (1992) we found increased IL-6 levels in 50% of tumorbearing animals. However, IL-6 was not measurable in tumorfree animals, irrespective of y-globulin treatment.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Kinetic studies of the effect of human immunoglobulin preparations on in vitro-induced monokine production indicated a sustained, significant inhibition of IL-6 production in the cultures supplemented with y-globulin (Anderson and Anderson, 1990). In agreement with Nadal et al (1992) we found increased IL-6 levels in 50% of tumorbearing animals. However, IL-6 was not measurable in tumorfree animals, irrespective of y-globulin treatment.…”
Section: Discussionsupporting
confidence: 91%
“…Human IL-6 has been detected in the serum of a majority of tumor-bearing SCID mice reconstituted with human tonsillar mononuclear cells, but not in any animals without human lymphoma (Nadal et al, 1992). IL-6 is a potent B-cellstimulating factor required for the growth of these cells and their terminal differentiation into Ig-secreting plasma cells (Hirano et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…The production of lymphoma in SC1D mice in our study is consistent with the report that spontaneous lym phomas occur in SCID mice even without any manipula tion [17], The development of B cell lymphoma of human MS cell origin in one of our mice is similar to the one that has been reported in SCID mice injected with human ton sillar mononuclear cells [19]. In that report the donors of human lymphomas were all seropositive for EBV, and EBV genome was detected in the B cell tumors.…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, the level of human IL-6 in mouse serum as produced by transferred human cells was higher in animals which received IL-1 in addition to the implant. The fact that human IL-6 is secreted by engrafted human cells in considerable amounts and can be detected in murine serum has also been described by other authors [29].…”
Section: Discussionmentioning
confidence: 65%